A Three-Site Clinical Feasibility Study of a Flexible Functional Electrical Stimulation System to Support Functional Task Practice for Upper Limb Recovery in People With Stroke - Smith, Christine; Sun, Mingxu; Kenney, Laurence; Howard, David; Luckie, Helen; Waring, Karen; Taylor, Paul; Merson, Earl; Finn, Stacey; Cotterill, Sarah (Frontiers in Neurology, 2019)
Introduction: Of those people who survive a stroke, only between 40% and 70% regain upper limb dexterity. A number of reviews have suggested that functional electrical stimulation (FES) may have a beneficial effect on upper limb motor recovery. In light of the promise offered by FES and the limitations with current systems a new system was developed (FES-UPP) to support people with stroke (PwS) to practice a range of voluntary controlled, FES-assisted functional activities. Objective: This paper reports on a three centre clinical investigation with the primary aim of demonstrating compliance of the new FES system with relevant essential requirements of the EU Medical Device Directive, namely to evaluate whether use of the FES-UPP enables PwS to perform a wider range of functional activities, and/or perform the same activities in an improved way. Design: Clinical investigation and feasibility study Settings: An in-patient stroke unit, a combined Early Supported Discharge (ESD) and community service, and an outpatient clinic and in-patient stroke unit. Participants: Nine therapists and 22 PwS with an impaired upper limb. Intervention: Every PwS was offered up to 8 sessions of FES-UPP therapy, each lasting approximately one hour, over a period of up to six weeks. Primary and secondary outcome measures: The operation, acceptability and feasibility of the interventions were assessed using video rating and the Wolf Motor Function Test Functional Ability Scale (WMF-FAS), direct observations of sessions and questionnaires for therapists and PwS. Results: The system enabled 24% (Rater A) and 28% (Rater B) of PwS to carry out a wider range of functional tasks and improved the way in which the tasks were performed (mean scores of 2.6 and 2.2 (with FES) versus mean scores 1.5 and 1.3 (without FES) (p<.05). Conclusion: The FES-UP proved feasible to use in three different clinical environments, with PwS who varied widely in their impairment levels and time since stroke. Therapists and therapy assistants from a wide range of backgrounds, with varying degrees of computer and/or FES knowledge, were able to use the system without on-site technical support.